2016
DOI: 10.1093/cid/ciw492
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Differential Non-Vaccine-Specific Immunological Effects of Diphtheria-Tetanus-Pertussis and Measles Vaccination

Abstract: Vaccines can have nontargeted heterologous effects that manifest as increased protection against nonvaccine infections, as described for measles vaccine (MV), or increased susceptibility to infections and death, as described following diphtheria-tetanus-whole cell pertussis (DTP) vaccination. The mechanisms are unknown, and high-quality immunological studies are lacking. This study was designed to investigate the heterologous effects of MV and DTP in 302 Gambian infants. The results support a sex-differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…The MV + DTP group also experienced a decline in naïve CD4 and CD8 T cell frequencies, and increased CD4 T EM and CD4 T EMRA populations following vaccination, with some sex differences in this effect. These results are consistent with our previous findings that combining MV with DTP vaccination has immune suppressing effects on PPD cellular responses and RNA expression in males, but the opposite effect in females, compared to giving DTP or MV alone ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The MV + DTP group also experienced a decline in naïve CD4 and CD8 T cell frequencies, and increased CD4 T EM and CD4 T EMRA populations following vaccination, with some sex differences in this effect. These results are consistent with our previous findings that combining MV with DTP vaccination has immune suppressing effects on PPD cellular responses and RNA expression in males, but the opposite effect in females, compared to giving DTP or MV alone ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…We previously showed that measles antibody titers 4 weeks after vaccination were not affected by simultaneous administration of DTP; nor were tetanus toxoid (Ttx), diphtheria toxoid (Dtx), and Ptx titers post-DTP vaccination altered by giving MV at the same time ( 17 ). To increase statistical power, we combined the MV and MV + DTP group to analyze for measles Ab correlations between baseline circulating Tregs and vaccine antibody levels 4 weeks later; and the DTP and MV + DTP groups to analyze for DTP Ab correlations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, time of vaccination has been linked to differences in T cell populations and strength and type of heterologous immune response (73,74). Sex-specific differences in terms of protective non-specific effects of vaccines such as measles and vaccinia (64,(75)(76)(77)(78)(79)(80) have also been described. Modification of vaccine composition (e.g., enrichment of particular proteins or epitopes) or conditions of administration (e.g., age, dose, number of immunizations) could potentially help us achieve the beneficial heterologous effects of vaccines without compromising their primary protective effects (vaccine specific).…”
Section: Implications For Vaccine Developmentmentioning
confidence: 99%